STANDARDIZING EDUCATION THROUGH NATIONAL EXAMINATION IN INDONESIA: THE REFLECTION OF PREVIOUS EXAMINATION POLICY - Alfian Alfian (Jurnal Scientia, 2023)
Indonesia is reforming its national education system in order to develop national educational quality. In response to this reform agenda the Ministry of Education and Culture has carried out several changes, such as National Examination which is one of the core components for mapping this quality standard. The objectives of examination) are based on the Ministry of National Education decree focus on measuring student achievement to inform educational quality at the provincial, regency, and school district level. The reform attempts to enhance educational accountability. In addition, the results of the examination were previously used as one of the determinants for student graduation. The examination is a semi-high-stake test where students’ success or failure raises psychological and ethical issues. Furthermore, the use of examination as the instrument to inform the educational quality is debatable. This paper aims to provide a critical analysis of the assessment policy using standardized test) in Indonesia by using Bacchi`s (2009) six questions of “what`s the problem represented to be” (WPR). This framework is used to explore what is the problem represented to be in standardized test examination policy in Indonesia secondary high school. The psychological and the ethical issues as well as an alternative assessment method for improving learning and educational quality will also be addressed at the end of this paper.